Roles of cytokines in the temporal changes of microglial membrane currents and neuronal excitability and synaptic efficacy in ATP-induced cortical injury model - Song, Bo kyung; Lee, S.J.; Kim, Chong Hyun (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Cytokines are important neuroinflammatory modulators in neurodegenerative brain disorders including traumatic brain injury (TBI) and stroke. However, their temporal effects on the physiological properties of microglia and neurons during the recovery period have been unclear. Here, using an ATP-induced cortical injury model, we characterized selective effects of ATP injection compared to needle-control. In the damaged region, the fluorescent intensity of CX3CR1-GFP (+) cells, as well as the cell density, was increased and the maturation of newborn BrdU (+) cells continued until 28 day-post-injection (dpi) of ATP. The excitability and synaptic E/I balance of neurons and the inward and outward membrane currents of microglia were increased at 3 dpi, when expressions of tumor necrosis factor (TNF)-α/interleukin (IL)-1β and IL-10/IL-4 were also enhanced. These changes of both cells at 3 dpi were mostly decayed at 7 dpi and were suppressed by any of IL-10, IL-4, suramin (P2 receptor inhibitor) and 4-AP (K+ channel blocker). Acute ATP application alone induced only small effects from both na？ve neurons and microglial cells in brain slice. How-ever, TNF-α alone effectively increased the excitability of na？ve neurons, which was blocked by suramin or 4-AP. TNF-α and IL-1β increased and decreased membrane currents of na？ve microglia, respectively. Our results suggest that ATP and TNF-α dominantly induce the physiological activi-ties of 3 dpi neurons and microglia, and IL-10 effectively suppresses such changes of both activated cells in K+ channel- and P2 receptor-dependent manner, while IL-4 suppresses neurons preferentially. ？ 2021 by the authors. Li-censee MDPI, Basel, Switzerland.